Performance, slaughter and serum biochemical variables of Vanaraja chicks in intensive farming system fed under different nutrient regimes - RAO, S V RAMA; RAJKUMAR, U; RAJU, M V L N; PRAKASH, B (The Indian Journal of Animal Sciences, 2018)
An experiment was conducted to study the performance of Vanaraja under intensive farming system with different nutrient regimes, i.e. Vanaraja standard (VSD), layer chick (LCD), layer grower (LGD) and broiler starter diet (BSD) up to 12 weeks of age. Dietary nutrient regimes significantly influenced the body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) up to 6 weeks of age. The BWG was significantly higher in groups fed BSD and LCD compared to those fed LGD during the initial 6 weeks of age. The BWG was significantly higher in Vanaraja birds fed BSD and LCD compared to other two groups at 7th week. The growth of birds fed VSD was significantly higher than those fed LGD. At the end of 12 weeks of age, BWG of birds was not affected due to dietary regimens. There was no significant variation in serum biological variables (total protein, albumin, globulin, cholesterol and triglycerides) at 6th and 12th week among the groups fed different dietary regimens. Relative weights of ready to cook yield, liver, abdominal fat and giblet were not affected with variation in nutrient regimen in diet. The Vanaraja birds gained uniform body weight without affecting slaughter variables at 12 weeks of age on diets containing diversified nutrient regime. The study concluded that Vanaraja birds can perform optimally with low nutrient diets resulting in reduced feed cost per unit weight gain.